Handbook on the digital creative economy. - Towse, Ruth; Handke, Christian (Cheltenham: Edward Elgar, 2013)
Digital technologies have transformed the way many creative works are generated, disseminated and used. They have made cultural products more accessible, challenged established business models and the copyright system, and blurred the boundary between producers and consumers. This unique resource presents an up-to-date overview of academic research on the impact of digitization in the creative sector of the economy.
Includes bibliographical references and index.
Keywords: Medios digitales; Capacidad creativa